Önkéntes jogkövetés az adó világában – hatékonyságvizsgálat a számok tükrében: VOLUNTARY COMPLIENCE IN TAXATION – EFFECTIVENESS CHECK IN FIGURES - dr. Antal, Anita (Közép-Európai Közlemények, 2021)
There is a research in the framework of the research workshop of Budapest Business School Zalaegerszeg Faculty of Business Administration, named “Micro and Macroeconomic Processes in the Past and Present”. It aims to examine the relationship between the major changes in the tax and tax procedure system and the legal consequences, as well as possible regularities. After examining the objectives of audit guidelines, the research work now focuses on the achievement of the objectives and the effectiveness of the audit activity. The improvement of tax morale is indicated by the increase in the revenues of the National Tax and Customs Authority (hereinafter: NAV), which is also considered significant as it occurred in a governmental effort to reduce public burdens. However, the increasingly "customer friendly" tax authority continues to take strong actions against those who violate tax liability elements. In the present study, in the light of the available data, I will examine the completion of voluntary compliance in the context of the effectiveness of control activities. In recent years, the most important aim of the NAV to encourage taxpayers to met their tax obligations correctly. To achieve this goal the tax authority has taken several steps. In 2018, the National Tax and Customs Reform Strategic Program (NAV 2.0) was launched, with the aim to make NAV one of the most efficient, integrated tax authorities in Europe by treating taxpayers as partners and reducing bureaucracy to realize tax revenues primarily through good behaviour incentives and the reduction of the size of black economy by 2021.